The Influence of Millennial Leadership and Corporate Social Responsibility (CSR) Disclosure on Firm Value with Firm Age as a Control Variable - Putu Cindra Permata Dewi; Anak Agung Gde Putu Widanaputra (International Journal of Economics, Management and Accounting, 2025)
Firm value is the company's performance reflected in the stock price, which is determined by the demand and supply in the capital market, representing public perception of the company's performance. This study aims to obtain empirical evidence on the influence of millennial leaders and CSR disclosure on firm value, with firm age as a control variable, in companies listed in the LQ45 Index from 2021 to 2023. The population of this study consists of 45 companies. Sampling was conducted using a non-probability sampling method with a purposive sampling technique, resulting in a total of 16 company samples. The analysis technique employed is multiple linear regression analysis. The results show that millennial leaders positively affect firm value, while CSR disclosure negatively affects firm value. This study provides theoretical implications by offering additional information and empirical evidence regarding the influence of millennial leaders and CSR disclosure on firm value. It also offers practical implications for company leaders to pay more attention to factors that can enhance firm value.